The Development of Students Worksheet Based on Problem- Based Learning to Escalate High Order Thinking Skills - T N. Irawati; M Mahmudah (Pancaran Pendidikan, 2020)
The present study was concerned with developing students’ worksheet (known as LKM), oriented to Problem-Based Learning. The worksheet was designed within the context of problems concerning higher-order thinking skills. The worksheet development applied the framework proposed by Dick and Carry, comprising of analysis, design, development or production, implementation or delivery, and evaluations. The findings of this study indicate that worksheets meet the validity standards with respect to the validity of the content, language, and presentation. The practicality and effectiveness of the worksheets are rated at high category, which is also corroborated by the excellent students’ responses.